2019
DOI: 10.1021/acs.langmuir.9b01242
|View full text |Cite
|
Sign up to set email alerts
|

Curious Results in the Prospective Binding Interactions of the Food Additive Tartrazine with β-Lactoglobulin

Abstract: The detailed characterizations of the binding interactions between food additive tartrazine (TZ) and β-lactoglobulin (β-LG) have been investigated through spectroscopic techniques combined with a molecular modeling study. A series of analyses, such as hyperchromic change in the UV–visible spectra, temperature-dependent quenching constant, time-resolved fluorescence, and Rayleigh scattering measurements, show that quenching of β-LG proceeds by a static quenching mechanism. TZ specifically binds with β-LG in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In the aliphatic region (3.0–4.5 ppm), the change of multiple peaks indicated that CFC was probably bound with aliphatic residues containing polar head groups (−OCH 3 , −NH 3 + , etc.) of β-LG via noncovalent interaction. , Compared with β-LG and BFCM, BFCC showed obvious changes of aromatic and aliphatic regions because of the covalent interaction between CFC and β-LG. Also, the disappearance of proton signals at 3.73–7.49 ppm (H of feruloyl groups) indicated the covalent conjugation between feruloyl groups of CFC and free amino groups of β-LG.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In the aliphatic region (3.0–4.5 ppm), the change of multiple peaks indicated that CFC was probably bound with aliphatic residues containing polar head groups (−OCH 3 , −NH 3 + , etc.) of β-LG via noncovalent interaction. , Compared with β-LG and BFCM, BFCC showed obvious changes of aromatic and aliphatic regions because of the covalent interaction between CFC and β-LG. Also, the disappearance of proton signals at 3.73–7.49 ppm (H of feruloyl groups) indicated the covalent conjugation between feruloyl groups of CFC and free amino groups of β-LG.…”
Section: Resultsmentioning
confidence: 93%
“…The difference in chemical shift between β-LG and BFCM was used to investigate the noncovalent interaction between CFC and β-LG. An apparent downfield shift was observed in the aromatic region of 1 H NMR spectra because of the noncovalent interaction, which probably induced the microenvironmental transformation of the aromatic residues of β-LG . In the aliphatic region (3.0–4.5 ppm), the change of multiple peaks indicated that CFC was probably bound with aliphatic residues containing polar head groups (−OCH 3 , −NH 3 + , etc.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BLG can also interact with various drugs and therefore has been proposed as a potential carrier for many therapeutic agents (Gholami et al, 2021;Ghalandari et al, 2015;Balasco et al, 2020;Kayani et al, 2018). Like most lipocalins, the -lactoglobulin molecule folds as an eight-stranded -barrel, which is the primary ligand-binding site (Allahdad et al, 2020;Dan et al, 2019;Loch et al, 2011Loch et al, , 2012Loch et al, , 2013Loch et al, , 2015Loch et al, , 2018Sawyer, 2013;Patel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous improvement of living standards, people have higher and higher requirements on the quality of food, which requires both delicacy and safety. Due to the continuous progress and development of biotechnology, the types of food additives are increasing, and the scope of their application in food production is also expanding [1][2]. The use of food additives has both advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%